Insight into the Structural Features of TSPO: Implications for Drug Development. (February 2020) - Lacapere, Jean-Jacques; Duma, Luminita; Finet, Stephanie; Kassiou, Michael; Papadopoulos, Vassilios
Abstract : The translocator protein (TSPO), an 18-kDa transmembrane protein primarily found in the outer mitochondrial membrane, is evolutionarily conserved and widely distributed across species. In mammals, TSPO has been described as a key member of a multiprotein complex involved in many putative functions and, over the years, several classes of ligand have been developed to modulate these functions. In this review, we consider the currently available atomic structures of mouse and bacterial TSPO and propose a rationale for the development of new ligands for the protein. We provide a review of TSPO monomeric and oligomeric states and their conformational flexibility, together with ligand-binding site and interaction mechanisms. These data are expected to help considerably the development of high-affinity ligands for TSPO-based therapies or diagnostics. Highlights: The transmembrane protein TSPO has been described as a diagnostic and therapeutic target for inflammation and, in particular, brain diseases. Various classes of TSPO ligand have been developed since its discovery in 1977, and some are routinely used for diagnosis and treatment. The design of new ligands is needed not only to improve cellular specificity, for instance to distinguish abnormal cells, but also for targeting to TSPO as part of a multiprotein complex of varying composition depending on the cell. Drug design will gain from TSPO structure–function analysis and computer simulation methods, such as molecular dynamics.